2002
DOI: 10.4049/jimmunol.168.8.3847
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying Differential Contribution of CD28 Versus Non-CD28 Costimulatory Molecules to IL-2 Promoter Activation

Abstract: T cell costimulation via CD28 and other (non-CD28) costimulatory molecules induces comparable levels of [3H]TdR incorporation, but fundamentally differs in the contribution to IL-2 production. In this study, we investigated the molecular basis underlying the difference between CD28 and non-CD28 costimulation for IL-2 gene expression. Resting T cells from a mutant mouse strain generated by replacing the IL-2 gene with a cDNA encoding green fluorescent protein were stimulated with a low dose of anti-CD3 plus ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 60 publications
3
30
0
Order By: Relevance
“…Moreover, CD28 costimulation sustains IL-2 promoter activation largely due to the activation of c-Rel binding to the CD28RE (44), although some other factors bind to this site, such as p65 and NF-AT (45). Of note, aly/aly mice also have a severe defect in IL-2 (Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CD28 costimulation sustains IL-2 promoter activation largely due to the activation of c-Rel binding to the CD28RE (44), although some other factors bind to this site, such as p65 and NF-AT (45). Of note, aly/aly mice also have a severe defect in IL-2 (Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on CD28 signaling demonstrated that it provides a potent signal for the up-regulation of several cytokines, at the level of both transcription and mRNA stability (20). A potential connection between CD28 and transcription factors for IL-2 production was suggested by the identification of the proximal IL-2 promoters, which confer responsiveness to anti-CD28 Abs in conjunction with anti-CD3 mAb or phorbol ester or ionophore (9,16,21,22). Despite several studies indicating that the NF-B pathway is perhaps the most relevant biochemical or transcriptional target for the costimulatory activity of CD28, important questions remain to be elucidated, including: what exactly are the CD28-specific signals upstream of I B kinase; is there recruitment of the IKK complex to CD28; and what are the protein kinase C-and Akt substrates in the NF-B pathway via CD28?…”
Section: Discussionmentioning
confidence: 99%
“…CD28 and non-CD28 costimulators have been reported to differ in this aspect (33)(34)(35). We therefore analyzed the IL-2 production induced by CD3 mAb alone or in combination with CD63 or CD28 mAbs.…”
Section: Costimulation Via Cd63 Induces Il-2 Production In T Cellsmentioning
confidence: 99%